(untitled) (Ameghiniana, 2014)
A revision of the Subfamily Crassatellinae Férussac, from the Paleogene–Neogene of Argentina is carried out.It is there represented by the genera Crassatella Lamarck, , Bathytormus Stewart, , Spissatella Finlay, and Talabrica Iredale,. Eight species are described and the new Talabrica elotroyoianae sp. nov. and Spissatella susanae sp. nov. are introduced. It is demonstrated that the genus Bathytormus is present in Patagonia and the record of Talabrica becomes the oldest known for the taxon, and the first beyond the Indo-Pacific area, where it was thought to be restricted to the Pliocene–Actual interval. Its occurrence in the Miocene of Patagonian indicates the presence of a Cenozoic disperser taxon, that having originated in the Patagonian latitudes during Miocene times, would have migrated through the Antarctic Circumpolar Current (CCA) towards New Zealand and Australia. In turn, Spissatella Finlay, would have moved through the CCA from New Zealand to Patagonia during Miocene times.